Instant Detection of Hydrogen Cyanide Gas and Cyanide Salts in Solid Matrices and Water by using CuII and NiII Complexes of Intramolecularly Hydrogen Bonded Zwitterions. Issue 42 (27th June 2018) - Nair, Ratish R.; Raju, M.; Jana, Kalyanashis; Mondal, Dhrubajyoti; Suresh, E.; Ganguly, Bishwajit; Chatterjee, Pabitra B.
Abstract: A series of intramolecularly hydrogen‐bonded zwitterionic compartmental ligandsHL1 –HL4, containing a pendent diamine arm that is monoprotonated and an aldehyde functionality at two different ortho ‐positions of a 4‐halophenoxide, is reported herein. Single‐crystal X‐ray diffraction (SXRD) provides persuasive evidence for the identification of this class of proton‐transferred zwitterions at room temperature. The solid‐state photoluminescent nature of these zwitterions remains intact in aqueous and organic solutions. Grinding ofHL1 andHL2 with Cu 2+ /Ni 2+ salts develop turn‐on probes1 –4 . Compounds1 and4 are dinuclear Cu II and Ni II species, respectively. Compound2 is a tetranuclear Cu II complex. Interestingly, compound3 is a mononuclear Ni II species in which both nitrogen atoms in the pendant diamine arm are protonated and, therefore, not coordinated to the Ni II center. All these probes (1 –4 ) display an instant response to the poison gas hydrogen cyanide (HCN) and cyanide salts present in both solid matrices and aqueous (100 % water) solution. Selective and rapid sensing of HCN gas and cyanide salts in solid/soil/water phases, without any interference, by the mechanosynthesized complexes1 –4 can be perceived easily by the naked eye under a hand‐held UV lamp. Abstract : Illuminating toxins : Solid‐state photoluminescent zwitterions function as probes for instant sensing of HCN gas and cyanide salts (see figure). A family of intramolecularly hydrogen‐bonded photoluminescent zwitterions, prepared directly from the precursors, upon reacting with Cu 2+ and Ni 2+ salts provide instantly responsive sensors for the poison gas hydrogen cyanide and cyanide salts present in both solid substances and water.